Official Kenyan High Altitude Training Center Web Site
Mt Kenya provides a special environment as one of the world`s masterpieces. As the Olympic gateway to the continent of Africa, Kenya and the Kenya International High Altitude Training Center (KHATC) will become the Mecca for athletes worldwide. Located at 7,000 feet on Mount Kenya, the Kenya International High Altitude Training Center will be a 310 acre training site. It will have a 10,000 square foot gym, two high-tech weight rooms, two running tracks and a sports medicine clinic. Mt. Kenya is located on the Equator and attracts athletes involved in mountain climbing, hiking, bicycling and, of course, running. Nanuki Township is situated at 6,800 feet above sea level. Athletes training at the KHATC can train at gradual altitudes up to and over 12,000 feet above sea level. Mt. Kenya and Nyanyuki Township have acted as the setting for a number of international films. For Kenyans, the KHATC has a far wider context in its unique development opportunity for the Kenyan people.